Contributions and limitations of a vision of the Peruvian 18th century: Criticism of "Aristocracia y Plebe. Lima, 1760-1830" by Alberto Flores Galindo - Chocano, Magdalena (1985)
Thinking of history as a form of total consciousness implies concern for a study of the past that allows us to understand the present. "Aristocracia y Plebe. Lima, 1760-1830" by Alberto Flores-Galindo (Mosca Azul Editores. Lima, 1984), is a text that is decidedly inclined towards this purpose, and this is its greatest merit. And, paradoxically, it reveals its greatest weakness. Topics that the author analyzes, such as racism and urban violence, lead us to a reflection that goes beyond the current situation; In this, they fully meet the objective of making the past an instrument for understanding the present. But the rationalization of that design also requires that we become aware of the preconceptions that contemporary experience inculcates, otherwise we will project them uncritically on the phenomena of the past.